2012
DOI: 10.1111/j.1365-2885.2012.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of stereoisomeric drugs with particular reference to bioequivalence determination

Abstract: Drugs containing one or more chiral centres exist in stereoisomeric molecular forms. Most commonly, drugs containing a single asymmetric carbon atom exist in two enantiomeric forms, designated as eutomer (the more potent) and distomer (the less potent). As well as differences in potency and other pharmacodynamic properties, most members of enantiomeric pairs commonly differ also in their pharmacokinetic profiles. This article reviews factors underlying differences in pharmacological properties of enantiomers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Another likely contributing process accounting for the differences between enantiomers in C max and AUC is first-pass metabolism [21]. As first-pass metabolism is an enzymatic process, it exhibits molecular recognition at saturable binding sites and would also give rise to interference between the enantiomers.…”
Section: Stereoisomer-mediated Pharmacokinetics Arising From First-pamentioning
confidence: 99%
See 2 more Smart Citations
“…Another likely contributing process accounting for the differences between enantiomers in C max and AUC is first-pass metabolism [21]. As first-pass metabolism is an enzymatic process, it exhibits molecular recognition at saturable binding sites and would also give rise to interference between the enantiomers.…”
Section: Stereoisomer-mediated Pharmacokinetics Arising From First-pamentioning
confidence: 99%
“…Indeed, inclusion of an inactive enantiomer provides nothing but an impurity or 'isomeric ballast, as coined by Ariens [16,20]. The resulting concern was stated by Lees et al [21]: "An impurity at the level 50% of the active constituent would never be tolerated by regulatory authorities for any other constituent, which is neither an active, nor excipient nor solvent. ".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potency has been defined as the amount of a drug required to produce an effect of a given intensity and the ‘potency ratio’ in vivo as the ratio of the doses producing effects of the same intensity (Lees et al. ). Research from rats, mice and humans suggest a potency ratio of 1:2 between racemic ketamine and S‐ketamine, while an experimental study in dogs indicated that the mean ratio of potency might be lower (1:1.29) in this species (Duque et al.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many studies have demonstrated that stereoisomers of a chiral drug often exhibited pronounced differences in their pharmacokinetic and metabolic profiles both quantitatively and qualitatively [16,123]. In addition to differences in potency and other pharmacodynamic properties, most members of enantiomeric pairs commonly differ also in their pharmacokinetic profiles [124,125]. A literature review indicates that stereoselective pharmacokinetics, rather than stereoselective pharmacological activity, is the main cause of differences in clinical efficacy between pure enantiomer and racemic proton-pump inhibitors.…”
Section: Pharmacokinetic Differences Between Enantiomersmentioning
confidence: 99%